2009
DOI: 10.2337/dc08-1755
|View full text |Cite
|
Sign up to set email alerts
|

Increased Risk of Acute Pancreatitis and Biliary Disease Observed in Patients With Type 2 Diabetes

Abstract: OBJECTIVE -The objective of this study was to assess the risk of acute pancreatitis in patients with type 2 diabetes compared with that in patients without diabetes. We also examined the risk of biliary disease (defined as occurrence of cholelithiasis, acute cholecystitis, or cholecystectomy), which is a major cause of pancreatitis.RESEARCH DESIGN AND METHODS -We conducted a retrospective cohort study using a large, geographically diverse U.S. health care claims database. Eligible patients (Ն18 years) were enr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

17
266
7
5

Year Published

2009
2009
2019
2019

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 397 publications
(295 citation statements)
references
References 17 publications
17
266
7
5
Order By: Relevance
“…A worldwide increase in aging of general population, metabolic syndrome, obesity, and diabetes mellitus is likely to cause an elevated risk of symptomatic biliary stone disease and subsequent requirement for the LC (7)(8)(9). As in other Western countries, obesity and closely associated type 2 diabetes are rapidly increasing in Finland (10,11).…”
Section: Introductionmentioning
confidence: 99%
“…A worldwide increase in aging of general population, metabolic syndrome, obesity, and diabetes mellitus is likely to cause an elevated risk of symptomatic biliary stone disease and subsequent requirement for the LC (7)(8)(9). As in other Western countries, obesity and closely associated type 2 diabetes are rapidly increasing in Finland (10,11).…”
Section: Introductionmentioning
confidence: 99%
“…Several clinical features associated with type 2 diabetes and obesity are recognized risk factors for acute pancreatitis (1). Recently, concerns have been raised regarding long-term consequences of incretin therapy in type 2 diabetic patients.…”
mentioning
confidence: 99%
“…Two large studies reported that patients with type 2 DM have 1.49-2.83 fold increased risk of acute pancreatitis compared to nondiabetics [2,3]. The exact cause of the increased risk of pancreatitis in diabetic patients is unclear, however, the known risk factors for pancreatitis appear more frequently in diabetic patients.…”
Section: Discussionmentioning
confidence: 99%
“…Other etiologic factors are biliary sludge and microlithiasis, smoking, hypertriglyceridemia, hypercalcemia, drugs, obesity, diabetes, infections and toxins, trauma, pancreas divisum, vascular disease, pregnancy and idiopathic [1]. Patients with diabetes mellitus have a 2 fold increase in the risk of pancreatitis due to factors such as obesity, gallstones, elevated triglycerides, and medications [2,3]. Obesity increases risk of pancreatitis and pancreas carcinoma due to increased inflammation [4].…”
mentioning
confidence: 99%